System of sticking diffusion particles of variable mass - Konarovskyi, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We construct a mathematical model of an infinite system of diffusion particles with interaction whose masses affect the diffusion coefficient. The particles begin to move from a certain stationary distribution of masses. Their motion is independent up to their meeting. Then the particles become stuck and their masses are added. As a result, the diffusion coefficient varies as a function inversely proportional to the square root of the mass. It is shown that the mass transported by particles is also characterized by a stationary distribution.